Establishing international best practice principles for impact assessment teaching and training. Issue 4 (3rd July 2020) - Morrison-Saunders, Angus; Pope, Jenny; Jones, Megan
ABSTRACT: Best Practice Principles for Impact Assessment (IA) Teaching and Training: were developed for the International Association for Impact Assessment (IAIA). Research conducted throughout 2018 and 2019 encompassed seven iterative steps: an initial practitioners workshop; comprehensive review of 40 years of literature on teaching IA; initial survey of teachers and trainers; follow-up interviews; development of draft set of principles; final survey of the importance of the draft principles to university teachers and professional development trainers in IA; and a final workshop at IAIA19. The resulting principles are grouped in relation to content (what is taught), pedagogy (how content is taught) and skills development. From 29 draft principles, those identified as 'Extremely Important' or Very Important' (28 in total) in the final survey were included in the Principles published by IAIA. Differences in relative importance of the principles are apparent between teachers and trainers, reflecting their different teaching contexts and objectives. It is hoped that the principles can contribute to more consistent and more effective IA education, contributing in turn to improved IA practice.